Rising sun : a novel - Crichton, Michael, 1942-2008 (Knopf : Distributed by Random House, 1992)
During the grand opening celebration of the new American headquarters of an immense Japanese conglomerate, the dead body of a beautiful woman is found. The investigation begins, and immediately becomes a headlong chase through a twisting maze of industrial intrigue and a violent business battle that takes no prisoners.